(997) The Institutional Framework of Socialist Foreign Trade Planning and the Way of Drawing Up the Plan الإطار المؤسسي لتخطيط التجارة الخارجية الاشتراكية وطريقة اعداد الخطة - Dieter Schulmeister. (معهد التخطيط القومى, 2021)
This is the second paper in the series of memos, dealing with socialist foreign trade planning as the basis of the organization of foreign trade in all socialist countries is the State monopoly of foreign trade. In conformity with the basic principles of planned economy also the foreign trade of German Democratic Republic is effected on the basis on this state foreign trade monopoly in connection with the currency and foreign trade transport monopoly.